Lungguh Krama Neggak Pendekatan Andragogi Pada Masyarakat Desa Sembiran Kecamatan Tejakula Kabupaten Singaraja - Eka Suadnyana, Ida Bagus Putu; Miarta Putra, I Nyoman (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
The Bali Aga social system in Sembiran Village is a local wisdom of the community which is maintained and preserved by the local community. Andragogy can play a role in education based on cultural values for teaching and learning in the context of teaching as cultural activity and the culture of teaching. This study will explore local wisdom, social systems and andragogy in the lungguh krama neggak system in Sembiran Village, three basic theoretical foundations were analyzed which were correlated with other theories, namely (convergence theory, structural functional theory and behavioristic theory. Data was collected by means of observation, interviews, and document studies using a research methodology that has been designed. Data were analyzed and processed systematically). descriptive research through three stages, namely data reduction, data presentation, and drawing conclusions.The results of this study indicate that the lungguh krama neggak system is based on the existence of three qualities in Sembiran Village, namely as a authorities Village, Traditional Village which is formed in accordance with state regulations and ancient Balinese traditional villages with the ulu apad system. Sembiran village has a very unique traditional social organization known as it's called ulu apad. Lungguh krama neggak is a system of social stratification of the indigenous people of Sembiran based on the order of marriage of its citizens. The forms of andragogy in the lungguh krama neggak system are reviewed from the principles of adult learning, adult learning needs, the function of community position in the lungguh krama neggak system.